TRADISI BASESOMBAU DALAM ADAT ISTIADAT MASYARAKAT MELAYU TAPUNG DI DESA SEKIJANG KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Sandy, Kurnia; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The Basesombau tradition is a one of the oral traditions that exist in the village of Sekijang, Tapung Hilir Sub-District,Kampar Regency, Riau Province. Which is carried out when there is a customary event such as in a traditional ceremony to enter the tribe, a traditional wedding ceremony, the coronation of Ninik Mamak and the appointment of Datuk Pucuk and others. Until now The Basesombau tradition is still maintained by prioritizing traditional ceremonies in an event because according to the Sekijang Village community they think they prioritize traditional activities over activities that are entertaintment in an event. The purpose of this research is to understand how the history of The Basesombau it self, so that we also know how the procession of The Basesombau tradition, understand the functions and values of The Basesombau tradition and the efforts made by traditional leaders and communities in Sekijang Village in preserving The Basesombau tradition today. The author uses qualitative research because this study looks at social and cultural behavior in the life of the Sekijang Village community from the process of The Basesombau traditional activities in traditional event.Data collection techniques are carried out by means of interview observation and documentation study then interpreted according to the context. The result of this study are that The Sekijang Village community maintains The Basesombau tradition, because this oral tradition has been carried out from generation to generation. Because in The Basesombau tradition there are various functions and values that can be used as guidelines in daily life and life in society.Keywords: The Basesombau Tradition, Function, Values, Processions, Sekijang Village Community